(untitled) (The Review of Diabetic Studies, 2025)
Objective. To propose and analyse an interdisciplinary model that integrates the practice of orthopaedics, physiotherapy and traumatology to optimise postoperative rehabilitation. Methods. A systematic literature review of the past five years was conducted, along with the design of a pilot study with 60 patients undergoing orthopedic surgery. Functional, pain, and recovery time variables were measured in two groups (interdisciplinary model versus conventional rehabilitation). Results. The interdisciplinary intervention group showed significantly greater improvements in functional recovery (p < 0.05), less pain, shorter length of stay in rehabilitation and lower rate of minor complications. Conclusions. The synergy between orthopedics, physiotherapy and traumatology under a structured model promotes better postoperative clinical results. Its progressive adoption and study in larger multicenter samples is recommended.